2021
DOI: 10.3390/cells10010140
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signalling in Alzheimer’s Disease: From Pathophysiological Regulation to Therapeutic Approaches

Abstract: Alzheimer’s disease (AD) is a neurodegenerative pathology representing a socioeconomic challenge, however, the complex mechanism behind the disease is not yet fully understood [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In CN samples, interestingly, among the most signi cant pathways enriched with signi cant CpGs is the KEGG pathway "Alzheimer's disease", which was curated based on recent AD literature and included genes that confer AD risks, such as APOE, PSENEN, MAPT, CALM3, MME, and others. Also, in CN samples, the most signi cant pathway is the calcium signaling pathway (P-value = 2.39 × 10 − 4 , FDR = 9.09 × 10 − 3 ), consistent with the calcium hypothesis of AD, which posits that dysregulated neuronal calcium homeostasis induces impaired synaptic plasticity, defective neurotransmission, promotes accumulation of Aβ and tau proteins, and subsequently lead to neuronal apoptosis in the brain 98,99 . Moreover, increased levels of free intracellular calcium have also been observed in normal aging, the strongest risk factor for AD 100,101 .…”
Section: Discussionsupporting
confidence: 66%
“…In CN samples, interestingly, among the most signi cant pathways enriched with signi cant CpGs is the KEGG pathway "Alzheimer's disease", which was curated based on recent AD literature and included genes that confer AD risks, such as APOE, PSENEN, MAPT, CALM3, MME, and others. Also, in CN samples, the most signi cant pathway is the calcium signaling pathway (P-value = 2.39 × 10 − 4 , FDR = 9.09 × 10 − 3 ), consistent with the calcium hypothesis of AD, which posits that dysregulated neuronal calcium homeostasis induces impaired synaptic plasticity, defective neurotransmission, promotes accumulation of Aβ and tau proteins, and subsequently lead to neuronal apoptosis in the brain 98,99 . Moreover, increased levels of free intracellular calcium have also been observed in normal aging, the strongest risk factor for AD 100,101 .…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, research on the pathogenesis of existing diseases can be used to guide future research on the neural circuit mechanisms of OCD. At pres- ent, research on neurodegenerative diseases such as Alzheimer's disease is relatively mature, with many related mechanism studies; [10][11][12][13] therefore, research on the mechanism of OCD has a high reference value.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been proposed that the Aβ small oligomers may penetrate [54] and aggregate within the membrane, forming unregulated and heterogeneous ion channels [55][56][57] which would allow ion dyshomeostasis [58], leading to cellular degeneration. In this context, it is useful to remind the reader that numerous studies [59][60][61] underline the important role of neuronal Ca 2+ dyshomeostasis in AD. A recent investigation [62] showed that oxidized membranes are prone to form native and oxidized domains which can induce a poration process [63].…”
Section: Discussionmentioning
confidence: 99%